Gendered Division of household labour and Care work during Covid-19 Outbreak: Evidence from Pakistan - Nayab Javed; Aurangzaib Alizai; Asma Seemi Malik, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
This study aims to check the impact of the COVID 19 outbreak on the gendered division of household labour and care work in Pakistan. In line with previous researches, this study has been carried out to examine situational changing patterns of gender roles in times of crisis. Previous literature depicts that women are more involved in unpaid work including household chores and care work. A sample of 469 men and women from different age groups, professions, marital statuses, and family types has been taken. Correlation analysis further shows that men are more involved in household chores than women however equally do care work. Moreover, men’s age, education, and leave from work have an impact on the division of household chores and care work. This demonstrates that Pakistani society has gendered division of household work which is evident in trend of being gender-neutral regarding unpaid work in households during Covid 19 outbreak.